Pharmacological treatment with L-DOPA may reduce striatal dopamine transporter binding in in vivo imaging studies - Nikolaus, S.; Antke, C.; Hautzel, H.; Mueller, H.-W. (Nuklearmedizin - NuclearMedicine, 2016)
Numerous neurologic and psychiatric conditions are treated with pharmacological compounds, which lead to an increase of synaptic dopamine (DA) levels. One example is the DA precursor L-3,4-dihydroxyphenylalanine (L-DOPA), which is converted to DA in the presynaptic terminal. If the increase of DA concentrations in the synaptic cleft leads to competition with exogenous radioligands for presynaptic binding sites, this may have implications for DA transporter (DAT) imaging studies in patients under DAergic medication.This paper gives an overview on those findings, which, so far, have been obtained on DAT binding in human Parkinson’s disease after treatment with L-DOPA. Findings, moreover, are related to results obtained on rats, mice or non-human primates. Results indicate that DAT imaging may be reduced in the striata of healthy animals, in the unlesioned striata of animal models of unilateral Parkinson’s disease and in less severly impaired striata of Parkinsonian patients, if animal or human subjects are under acute or subchronic treatment with L-DOPA. If also striatal DAT binding is susceptible to alterations of synaptic DA levels, this may allow to quantify DA reuptake in analogy to DA release by assessing the competition between endogenous DA and the administered exogenous DAT radioligand.
Keywords: Dopamine; L-DOPA; dopamine transporter; dopamine reuptake; Parkinson’s disease